2021
DOI: 10.3233/jnd-210720
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin 5 Knockout Mouse Model Recapitulates LGMD2L Muscle Pathology and Offers Insight Into in vivo Functional Deficits

Abstract: Mutations in the Anoctamin 5 (Ano5) gene that result in the lack of expression or function of ANO5 protein, cause Limb Girdle Muscular Dystrophy (LGMD) 2L/R12, and Miyoshi Muscular Dystrophy (MMD3). However, the dystrophic phenotype observed in patient muscles is not uniformly recapitulated by ANO5 knockout in animal models of LGMD2L. Here we describe the generation of a mouse model of LGMD2L generated by targeted out-of-frame deletion of the Ano5 gene. This model shows progressive muscle loss, increased muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…While, the first four genes encode for ATPases involved in ions transport, like Ca 2+ or H + /K + , ANO5 encodes for an anoctamin, which belongs to a protein family of Ca 2+ activated chlorine channels and phospholipid scramblases 34 A founder mutation in ANO5 has been implicated in muscular dystrophy 34 . Despite the high expression in brain and the controversial muscle phenotype in the mouse knockout models 35 , 36 , its function in the brain remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the first four genes encode for ATPases involved in ions transport, like Ca 2+ or H + /K + , ANO5 encodes for an anoctamin, which belongs to a protein family of Ca 2+ activated chlorine channels and phospholipid scramblases 34 A founder mutation in ANO5 has been implicated in muscular dystrophy 34 . Despite the high expression in brain and the controversial muscle phenotype in the mouse knockout models 35 , 36 , its function in the brain remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…A founder mutation in ANO5 has been implicated in muscular dystrophy 34 . Despite the high expression in brain and the controversial muscle phenotype in the mouse knockout models 35,36 , its function in the brain remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…ANO5 is located in intracellular vesicles and the sarcoplasmic or endoplasmic reticulum [ 14 ]. Despite its putative calcium-activated chloride channel property, the study of chloride currents in ANO5-deficient mice showed similar channel activity to their wild-type littermates [ 34 , 35 ]. ANO5 functions predominantly in phospholipid scrambling (PLS), which facilitates the movement of phospholipids between the membrane bilayer during various biological processes [ 36 ].…”
Section: Gene and Proteinmentioning
confidence: 99%
“…Two initial mouse models of anoctaminopathy-5 that were created by the complete disruption of Ano5 failed to show significant clinical myopathy or cardiomyopathy [ 69 , 70 ]. Later on, mouse models achieved by truncated ANO5 expression showed a myopathic phenotype, including variable degrees of weakness and muscle atrophy, exercise intolerance, and myofiber injury, as a result of defective membrane repair machinery [ 35 , 36 ]. The transduction of AAV- Ano5 into the knock-out mice rescued the membrane repair defect [ 36 ].…”
Section: Animal Modelsmentioning
confidence: 99%
“…As an integral membrane glycoprotein, ANO5 may function as a calcium‐activated chloride channel (CaCC) or phospholipid scramblase. However, a pertinent hallmark of ANO5 needs to be exploited in view of its location in intracellular vesicles, endoplasmic reticulum, Golgi apparatus and endosomes of skeletal muscle and bone tissues (Benarroch, 2017; Brunner et al, 2014; Foltz et al, 2021; Li, Wang, Chen, et al, 2022; Li, Wang, Wang, et al, 2022; Pedemonte & Galietta, 2014; Suzuki et al, 2013; Thiruvengadam et al, 2021). In addition to GDD, recessive mutations in ANO5 are associated with two kinds of muscular dystrophy (MD) disorders: limb‐girdle muscular dystrophy‐2L (LGMD2L) and Miyoshi muscular dystrophy‐3 (MDD3) (Di Zanni et al, 2020; Penttila et al, 2012; Thiruvengadam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%